[OA052] Proton minibeam radiation therapy: A promising alternative for high-grade gliomas. (August 2018) - Prezado, Yolanda; Gonzalez, Wilfredo; Patriarca, Annalisa; Jouvion, Gregory; Guardiola, Consuelo; Nauraye, Catherine; Labiod, Dalila; Juchaux, Marjorie; Jourdain, Laurene; Sebrié, Catherine; Pouzoulet, Frederic
Abstract : Introduction: The morbidity of normal tissues continues being the main limitation in radiotherapy. To overcome it, we proposed a novel concept: proton minibeam radiation therapy (pMBRT)[1] . It allies the physical advantages of protons with the normal tissue preservation observed when irradiated with submillimetric spatially fractionated beams (minibeam radiation therapy). We have recently implemented this technique[2] at a clinical center and demonstrated that pMBRT leads to a significant increase of normal tissue tolerances[3] with respect to standard proton therapy. This work aimed at showing that this gain allows using potentially curative doses in the cases of radioresistant tumors, like gliomas. Material and methods: Two groups of rats were implanted with RG2 rat glioma cells intracranially. Half of the animals received a whole brain irradiation (pMBRT). The dose distributions were completely inhomogeneous, with areas of very high doses in the minibeam paths (70 Gy in one fraction) and areas of low doses in the spaces between minibeams (around 10 Gy). A third group ( n  = 8) of normal rats were irradiated (whole brain) in the same configuration and followed for 6 months. Results: The controls presented a mean survival time of 20.8 ± 0.4. The group receiving pMBRT showed a substantial increase of mean survival time (as today, a factor 2 gain with respect to the controls). The existence of several long term survivals indicates tumor sterilization. The irradiated normal rats exhibited no clinical symptoms for 6 months after irradiation in contrast to rats irradiated in previous studies with lower doses [4]. No substantial damage was observed in the MRI evaluation. Conclusions: These results indicate that pMBRT widens the therapeutic window for gliomas. The fact that a significant tumor control is reached even with inhomogeneous dose distributions contradicts the classical paradigm of standard radiotherapy and points at the participation of distinct radiobiological mechanisms.